2018
DOI: 10.1128/mbio.00430-18
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the I38T PA Substitution as a Resistance Marker for Next-Generation Influenza Virus Endonuclease Inhibitors

Abstract: The clinical severity and annual occurrence of influenza virus epidemics, combined with the availability of just a single class of antivirals to treat infections, underscores the urgent need to develop new anti-influenza drugs. The endonuclease activity within the viral acidic polymerase (PA) protein is an attractive target for drug discovery due to the critical role it plays in viral gene transcription. RO-7 is a next-generation PA endonuclease inhibitor of influenza A and B viruses, but its drug resistance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 26 publications
(42 reference statements)
7
57
0
Order By: Relevance
“…This high-throughput focus-forming assay was compared against the plaque assay for its ability to detect reduced susceptibility to baloxavir acid (the active form of baloxavir marboxil) among reference strains. The reference strains included viruses with and without the I38T substitution, which conferred a 40-to 50-fold reduction in susceptibility to baloxavir in both assays, consistent with the fold change observed for this substitution in other studies (Jones et al, 2018;Omoto et al, 2018). A panel of NAI-resistant viruses and their sensitive counterparts were also evaluated for their susceptibility in both assays, which showed similar results and validated the focus-forming assay as an adequate surveillance tool.…”
Section: Susceptibility Of Influenza Viruses To the Novel Cap-dependesupporting
confidence: 76%
See 1 more Smart Citation
“…This high-throughput focus-forming assay was compared against the plaque assay for its ability to detect reduced susceptibility to baloxavir acid (the active form of baloxavir marboxil) among reference strains. The reference strains included viruses with and without the I38T substitution, which conferred a 40-to 50-fold reduction in susceptibility to baloxavir in both assays, consistent with the fold change observed for this substitution in other studies (Jones et al, 2018;Omoto et al, 2018). A panel of NAI-resistant viruses and their sensitive counterparts were also evaluated for their susceptibility in both assays, which showed similar results and validated the focus-forming assay as an adequate surveillance tool.…”
Section: Susceptibility Of Influenza Viruses To the Novel Cap-dependesupporting
confidence: 76%
“…Selection studies in cell culture and analysis of viruses from drugtreated patients in clinical trials have revealed the principal pathways to reduced susceptibility to baloxavir Jones et al, 2018;Omoto et al, 2018) and pimodivir (Byrn et al, 2015;Trevejo et al, 2018). In baloxavir studies, treatment-emergent amino acid substitutions most frequently occurred at conserved position I38 (I38 F/ M/T) in the PA endonuclease active site and conferred reduced susceptibility by 10-57-fold in influenza A and 2-6-fold in influenza B. Substitutions at position S324 (S324C/I/N/R) in the cap-binding site of PB2 were recognized as the leading pathway for a 60-160-fold reduced susceptibility to pimodivir.…”
Section: Methods For Testing Influenza Virus Susceptibility To Novel mentioning
confidence: 99%
“…Baloxavir marboxil (Xofluza®) is a recently approved prodrug that targets the cap‐snatching endonuclease. However, resistance to Xofluza® has been reported in both clinical and in vitro systems, but with a significant decrease in viral fitness …”
Section: Introductionmentioning
confidence: 99%
“…Variants (I38T, I38F, and E23K) with reduced susceptibility to baloxavir marboxil were isolated from treated patients during phase II clinical trials . The same I38T PA substitution also caused resistance of influenza A(H1N1) viruses serially passaged in MDCK cells with RO‐7, an investigational endonuclease inhibitor that is similar but not identical to baloxavir marboxil …”
Section: Introductionmentioning
confidence: 99%
“…19 The same I38T PA substitution also caused resistance of influenza A(H1N1) viruses serially passaged in MDCK cells with an investigational endonuclease inhibitor that is similar but not identical to baloxavir marboxil. 20 Umifenovir (C 22 transition to its fusogenic state, and prevents HA-mediated membrane fusion during influenza virus infection. 21 Co-crystal structure of umifenovir with the influenza virus HA glycoprotein indicates that umifenovir binds in a hydrophobic cavity at the interface of the HA protomers in the upper region of the stem.…”
mentioning
confidence: 99%